Diastolic stress test echocardiography in patients with hypertrophy cardiomyopathy: association with exercise capacity. (25th November 2020) - Fava, A.M; Sande Mathias, I; Alashi, A; Saijo, Y; Popovic, Z; Thamilarasan, M; Lever, H; Desai, M.Y
Abstract: Background: Diastolic dysfunction (DD) is a frequent occurrence in hypertrophic cardiomyopathy (HCM) patients. Symptoms of DD are often unmasked only during exercise, as left ventricular (LV) filling pressure is normal at rest. Purpose: We sought to establish if abnormal DST parameters are associated with reduced exercise capacity in HCM patients. Methods: We examined 590 asymptomatic/minimally symptomatic HCM patients (54±14 years, 57% men, body mass index 30±6 kg/m 2, 84% on beta-blockers) with HCM by echocardiography at rest & maximal exercise. Septal and lateral [e'] mitral annular velocity, peak early [E] and late [A] mitral inflow velocity, Mitral E/e' and left atrial volume index (LAVI) was recorded. Exercise functional capacity was stablished as age-gender predicted metabolic equivalents (AGP-METs). Results: Echocardiography at rest had LVEF of 62±6, wall thickness of 16.7±0.5 mm, LVMI of 111±43 g m –2, LVOT gradient of 26±33 mmHg, LAVI 34.5±17 mm, E/A ratio of 1.2±0.6, and average E/e' ratio 12.7±0.6. Following maximal exercise had a mean LVOT gradient of 61±59 mmHg, E/A ratio of 1.2±1.0 and average E/e' ratio 12.7±1.0. Only 42% had >85% of age-sex predicted METs. Logistic regression analysis testing the association between various predictors and 85% AGP-METs are shown in table 1. Conclusion: There is a significant association between abnormal diastolic response to exercise and reduced exercise capacity in patients with HCM. Funding Acknowledgement: Type of funding source: None